Analysis of the use of website based learning media at the elementary school level - Dian Putra, Agung; Nurjanah, Siti; Profithasari, Nindy (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
Modern education makes digital based learning media the primary choice in the learning process. Educators must create media that adjusts to the character of the learners and their ability to innovate in learning media. Website based learning media is one among many digital learning media that can be used. The analysis of the use of this media at the Elementary School level needs to be examined to see its advantages and disadvantages so that it can be applied by every educator in the future. The analysis was conducted using a qualitative approach and data collection through document studies. The results show that the use of web-based learning media at the elementary school level is appropriate due to its attractive visualization and ease of use. The ability of educators to create innovative website based learning media can have a positive impact on the process and outcomes of learning.